Risk and Management of Patients with Cancer and Heart Disease - Hill, Loreena Michelle; Delgado, Bruno; Lambrinou, Ekaterini; Mannion, Tara; Harbinson, Mark; McCune, Claire (My University, 2023)
Cancer and cardiovascular disease are two of the leading causes of global mortality and morbidity. Medical research has generated powerful lifesaving treatments for patients with cancer; however, such treatments may sometimes be at the expense of the patient's myocardium, leading to heart failure. Anti-cancer drugs, including anthracyclines, can result in deleterious cardiac effects, significantly impacting patients' functional capacity, mental well-being, and quality of life. Recognizing this, recent international guidelines and expert papers published recommendations on risk stratification and care delivery, including that of cardio-oncology services. This review will summarize key evidence with a focus on anthracycline therapy, providing clinical guidance for the non-oncology professional caring for a patient with cancer and heart failure.
Keywords: Anthracycline; Cardiotoxicity; Heart failure; Risk stratification